High temperature lubrication of ceramics by surface modification - Wei, William; Lankford, James; Singer, Irwin; Kossowsky, Ram (Surface & coatings technology, 1989)
Results of recent investigations on the friction and wear of ceramics have shown that the surface modification of structural ceramics is an extremely promising method for the high temperature self-lubrication of these materials. Further development of such advanced ceramics requires an understanding of the chemistry and mechanical properties of the tribological films which form on and lubricate the ceramics. In this paper an overview is presented of critical issues which must be addressed in this area. In addition, a phenomenological model of the lubricating properties of such films is discussed in light of recent results on ion-beam-modified Si 3N 4 and partially stabilized zirconia and of current knowledge of surface modification chemistry and structure.